2011
DOI: 10.2528/pierl11033001
|View full text |Cite
|
Sign up to set email alerts
|

A NOVEL MINIATURIZED BANDPASS FILTER BASED ON COMPLEMENTARY SPLIT RING RESONATORS (CSRRs) AND OPEN-LOOP RESONATORS

Abstract: A microstrip bandpass filter is presented based on Complementary Split Ring Resonators (CSRRs) and a pair of openloop resonators that has a single pair of transmission zeros at finite frequencies that causes an improvement at skirt response. An equivalent circuit is introduced to make analysis and optimization faster. Finally a filter is designed using the proposed cell and the simulation results with both equivalent model and full wave analysis are in very good agreement. The filter was fabricated and the mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Furthermore, the negative permeability is transformed to a negative permittivity in the case of the CSRR . This negative permittivity behavior of the medium can have great potential applications to design planar filters , to fabricate different category of antennas such as compact antennas , circularly polarized antennas , and dual‐band antennas . Besides, CSRR offer improved performance, gain enhancement for antenna and antenna miniaturization .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the negative permeability is transformed to a negative permittivity in the case of the CSRR . This negative permittivity behavior of the medium can have great potential applications to design planar filters , to fabricate different category of antennas such as compact antennas , circularly polarized antennas , and dual‐band antennas . Besides, CSRR offer improved performance, gain enhancement for antenna and antenna miniaturization .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of SRRs for designing small antennas is of great interest. By considering the concepts of duality, the negative permittivity nature of CSRR can be derived from the negative permeability nature of SRR in a straightforward way, which has strong potential applications in designing simple planar filters [4][5][6], compact antennas [7][8][9], circularly polarized antennas [10,11] and dual-band antennas [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst various topologies available, ringbased topology is well known for its dual mode capability, compact size and sharp rejection skirts [1][2][3][4][5][6][7][8][9][10]. Early work done by Wolff had shown that, two degenerate orthogonal modes, TM 10 and TM 01 coexist in a symmetrical ring resonator [1].…”
Section: Introductionmentioning
confidence: 99%
“…In order to generate the dual resonance, most of the dual-mode ring resonator topologies require adjustment of their coupling points and perturbation elements [2][3][4][5][6][7][8]. The work reported by [9,10] made use of quarter-wavelength coupled lines in the ring topology that led to a global synthesis, based on the control parameters: Z r , Z oe and Z oo , which are the impedance of the ring, and the even-and oddmode impedance of the coupled lines, respectively.…”
Section: Introductionmentioning
confidence: 99%